2012
DOI: 10.1097/ijg.0b013e31820d7d19
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Increased Intraocular Pressure Related to Intravitreal Antivascular Endothelial Growth Factor Therapy for Neovascular Age-related Macular Degeneration

Abstract: Serial injections of anti-VEGF agents may lead to persistent IOP elevations that require glaucoma therapy. The clinician should recognize this phenomenon, as it can occur even if the patient has tolerated multiple prior injections without IOP elevation. Further exploration of the relationship between anti-VEGF therapy and IOP is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 25 publications
5
87
0
7
Order By: Relevance
“…Choi et al [22] investigated 127 patients treated with bevacizumab, ranibizumab or pegaptanib and found 9.4% of the patients who devolved IOPs of >25 mm Hg. In another study, Tseng et al [23 ]present a series of 25 eyes of 23 patients who developed increased IOP due to repeated anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al [22] investigated 127 patients treated with bevacizumab, ranibizumab or pegaptanib and found 9.4% of the patients who devolved IOPs of >25 mm Hg. In another study, Tseng et al [23 ]present a series of 25 eyes of 23 patients who developed increased IOP due to repeated anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The ANCHOR [8] and PIER [10] study groups reported a transient rise in IOP which reverted back to baseline within hours of injection. Numerous other groups reported transient or even sustained elevation of IOP after intravitreal anti-VEGF therapy [15,16,17,18,19,20,21,22,23]. Our study aimed to investigate whether there is a long-term effect on IOP in AMD patients who received multiple IVTs at the different points of treatment duration.…”
Section: Introductionmentioning
confidence: 99%
“…74,75 While some patients respond to intravitreal injection with sustained elevation of IOP, most do not even after multiple injections. [76][77][78][79][80][81][82] In our study, we performed intravitreal injection of drug-loaded NS once and observed IOPlowering effects out to 32 days (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…The procedure is relatively safe, despite occasional reports of glaucoma, cataract and central retinal artery occlusion [18,19]. Further hazards of anti-VEGF treatment include hyphema and long term IOP elevation with serial injections [20]. The long term effectivity of Bevacizumab in controlling IOP is uncertain.…”
Section: Anti-vegf Therapymentioning
confidence: 99%